PERANAN ORANG TUA DALAM PEMBINAAN MORAL ANAK REMAJA DI KELURAHAN KAWANGKOAN BAWAH KECAMATAN AMURANG BARAT - Wajongkere, Julia; Tasik, Femmy C. M.; Tumengkol, Selvie M. (HOLISTIK, Journal Of Social and Culture, 2021)
Association is an interaction between several people either in the form of family, organization or community. Through association we will develop because we know about the ordinances of associating. Thus making individuals social because basically humans are social beings. But the association in this modernization era has been misinterpreted especially among young people. Parenting includes not only actions but also what we want our children to understand about life. What it means to live and as to live this life well.Every child needs to know they are loved and loved by parents wholeheartedly, although on the contrary every parent must love and love the child without any conditions. Both the bad nature and attitude of the child, they must accept the shortcomings and advantages possessed by the child.The method used is qualitative method because in this study trying to find answers to questions related to the feelings of parents in fostering the morale of adolescents in Kawangkoan Bawah Village.Parents' attention to the development of adolescents in the direction of maturity in Kawangkoan Bawah Subdistrict Amurang Barat is very important but not yet fully, as expected. Therefore, the attention of parents is generally centered on meeting the needs of.Â Keywords: parents, coaching, young people